RESPON PEMBERIAN BERBAGAI DOSIS BIOURINE PLUS DAN PUPUK KIMIA MAJEMUK PADA PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonocum L.) - Dian Eka Kusumawati; Mariyatul Qibtiyah; Afifatul Masrurroh (AGRORADIX : Jurnal Ilmu Pertanian, 2023)
Shallots (Allium ascalonicum L.) are seasonal vegetables that are in great demand by the public as a staple food seasoning. Shallot production is seasonal but demand tends to be every day. This condition creates an imbalance between supply and demand for shallots. Efforts to increase the growth and production of shallots are by providing the right nutrients. Therefore, research on types of chemical compound fertilizers and doses of biourine plus is very important to do, the purpose of this study is to determine the effect of types of compound chemical fertilizers and doses of biourine plus on the growth and production of shallots. This research was conducted in Bogangin Village, Sumberrejo District, Bojonegoro Regency from January to March 2022. This research was conducted by using the Factorial Randomized Block Design (RAK) method, which consisted of 2 factors and each factor consisted of 3 levels with 3 replications. The first factor is compound chemical fertilizers: Phonska fertilizer, Yaramila NPK fertilizer and Saprodap fertilizer. The second factor was the dose of biourine plus: control (without biourne plus), 1000 l/ha and 1500 l/ha. Observational data from each parameter were analyzed with Fisher's test (F test) 5% and if there was a significant difference, it was continued with the Least Significant Difference test (BNT 5%). The results of this study showed that the application of NPK Yaramila fertilizer and a dose of biourine plus 1000 l/ha produced the best results compared to other treatments.